Towns conquer: a gamified application to collect geographical names (vernacular names/toponyms) - Castellote, Jesus; Huerta, Joaquin; Pescador, Javier; Brown, Michael (2013)
The traditional model for geospatial crowd sourcing asks the public to use their free time collecting geospatial data for no obvious reward. This model has shown to work very well on projects such as Open Street Map, but comes with some clear disadvantages such as reliance on small communities of ‘Neo-geographers’ and variability in quality and content of collected data. This project aims at tackling these problems by providing alternative motivation specifically a smartphone based computer game service. Geographical names (vernacular names/ toponyms) have been identified as potential targets as they are difficult to collect on a large scale and easy to collect locally, thus ideal for crowd sourcing. The data set will be a toponyms database provided by the Spanish National Geographic Institute (IGN Spain). A location based game is targeted as it is easy to guide data collection with in-game rewards (prizes, points, badges etc.). Android is chosen for its accessible API and wide use.